PENGEMBANGAN MODUL PEMBELAJARAN TEMATIK BERBASIS SAINTIFIK PADA TEMA PERISTIWA DALAM KEHIDUPAN DI SEKOLAH DASAR - Anggraini, Susi (Jurnal Visi Ilmu Pendidikan, 2020)
AbstractThis research is a development research that uses 4D model consist of define, desain, develope, and disseminate. This study aims to study scientific-thematic learning modules. Data collection techniques in this research are observation techniques and interview techniques. The subjects research were students in grade V SDN 7 Sungai Raya. The research produces scientific thematic learning modules that the validity level with an average validity by material experts at 3.56, validity by media experts at 3.54 and validity by design experts at 3.65 which allows thematic module is valid. Student responses to modules reached an average of 3.31. This module shows valid and suitable for use.Keyword: Module, Thematic Learning, 4D Model.